2012 45th Annual IEEE/ACM International Symposium on Microarchitecture 2012
DOI: 10.1109/micro.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Energy Characterization of CMP/SMT Processor Systems via Automated Micro-Benchmarks

Abstract: Microprocessor-based systems today are composed of multi-core, multi-threaded processors with complex cache hierarchies and gigabytes of main memory. Accurate characterization of such a system, through predictive pre-silicon modeling and/or diagnostic postsilicon measurement based analysis are increasingly cumbersome and error prone. This is especially true of energy-related characterization studies. In this paper, we take the position that automated micro-benchmarks generated with particular objectives in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 46 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…We demonstrated that validating a power model at the core or chip level hides a large amount of internal error at the unit level and below. Targeted microbenchmarking is a well-known technique for characterizing fine-grained power [1,27,45]. 2.…”
Section: Discussion and Guidelinesmentioning
confidence: 99%
“…We demonstrated that validating a power model at the core or chip level hides a large amount of internal error at the unit level and below. Targeted microbenchmarking is a well-known technique for characterizing fine-grained power [1,27,45]. 2.…”
Section: Discussion and Guidelinesmentioning
confidence: 99%
“…Activity proxies constitute a well-known technique to estimate or track the power consumption profile of processor chips [12][13][14][15][16]. In the z13 design, they consist of a set of 16 activity counters.…”
Section: Activity Proxiesmentioning
confidence: 99%
“…The methodology is centered around the use of an automated microbenchmark generation toolset called MicroProbe [12].…”
Section: Power-management Characterization Through Automated Microbenmentioning
confidence: 99%
See 2 more Smart Citations